2017
DOI: 10.1111/bph.13976
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate protects against disruption of the blood‐milk barrier and moderates inflammatory responses in a model of mastitis induced by lipopolysaccharide

Abstract: Short-chain fatty acids are fermentation end products produced by gut bacteria, which have been shown to ameliorate inflammatory bowel diseases and allergic asthma. However, the mechanism involved remains largely unknown. Here, we investigate the protective effects and mechanisms of sodium butyrate (SB) on LPS-induced mastitis model. EXPERIMENTAL APPROACHEffects of increasing doses of SB on blood-milk barrier function and inflammation are studied in BALB/c mice with LPS-induced mastitis. The underlying mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 58 publications
8
68
0
Order By: Relevance
“…These data agree with recent data in ruminal epithelium and bovine hepatocytes (Dai et al, 2017;Xu et al, 2018). In the absence of an inflammatory challenge, the viability of mouse mammary epithelial cells was not affected by 0.1 to 2 mM SB treatment for 18 h (Wang et al, 2017). Thus, together, the available data suggest that -T) were treated with 1 µg/mL LPS for 6 h; with different concentrations of trichostatin A (TSA; 6.25, 12.5, 25, or 50 nM) for 18 h, followed by a challenge with 1 µg/mL LPS for an additional 6 h; with amounts of solvent [0.1% (vol/vol) ethanol, vehicle control (Veh)] equal to that present in TSA cultures for 18 h, followed by a challenge with 1 µg/mL LPS for an additional 6 h; or with different concentrations of SB (0.1, 0.25, 0.5, 1, 2, or 5 mM) for 18 h, followed by a challenge with 1 µg/mL LPS for an additional 6 h. the anti-inflammatory effect of SB is not due to differences in cell numbers before LPS challenge.…”
Section: Discussionsupporting
confidence: 92%
“…These data agree with recent data in ruminal epithelium and bovine hepatocytes (Dai et al, 2017;Xu et al, 2018). In the absence of an inflammatory challenge, the viability of mouse mammary epithelial cells was not affected by 0.1 to 2 mM SB treatment for 18 h (Wang et al, 2017). Thus, together, the available data suggest that -T) were treated with 1 µg/mL LPS for 6 h; with different concentrations of trichostatin A (TSA; 6.25, 12.5, 25, or 50 nM) for 18 h, followed by a challenge with 1 µg/mL LPS for an additional 6 h; with amounts of solvent [0.1% (vol/vol) ethanol, vehicle control (Veh)] equal to that present in TSA cultures for 18 h, followed by a challenge with 1 µg/mL LPS for an additional 6 h; or with different concentrations of SB (0.1, 0.25, 0.5, 1, 2, or 5 mM) for 18 h, followed by a challenge with 1 µg/mL LPS for an additional 6 h. the anti-inflammatory effect of SB is not due to differences in cell numbers before LPS challenge.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the modulation of SB in NF‐κB activity and proinflammatory cytokines production may also be related to its inhibition of the activity of class Ι HDACs (HDAC1, HDAC2 and HDAC3) 22 . A previous study showed that SB protected against LPS‐induced mastitis by inhibition of HDACs, which subsequently inhibited NF‐κB activity 40 . Meanwhile, a study showed that HDAC3 deletion impaired the IFN‐β‐dependent signal in LPS‐induced macrophages, suggesting that HDAC3 plays a critical role in inflammation gene expression in macrophages 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages and MECs work in concert to recruit polymorphonuclear neutrophils (PMNs) to the tissue, which help combat the pathogen via phagocytosis and reactive oxygen species-(ROS-) mediated destruction in addition to cytokine production that supports a proinflammatory and antimicrobial environment [11]. These actions that resolve the infections are not without costs as the tight junctions of MECs loosen as a result of proinflammatory signaling and PMN diapedesis [12,13]. Some of the MECs undergo apoptosis because of these stresses which induce caspase 3 expression or activation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its large economic impact to dairy industry, mastitis research has become an increasingly progressive field as many look to the pathology of this disease and find therapeutic treatments to combat it. The most common approach to study mastitis has been through an intramammary infusion of proinflammatory bacteria toxin into the mammary gland using bovine and rodent models [12,20,21]. While they do not exactly mimic bovine lactation, mice and rats have widely been used for mastitis models for over 40 years because of their advantages of easier maintenance and cost effectiveness compared to bovine counterpart [22].…”
Section: Introductionmentioning
confidence: 99%